Effects of extraction conditions over the phlorotannin content and antioxidant activity of extract from brown algae Sargassum serratum (Nguyen Huu Dai 2004) - Boi, Vu Ngoc; Cuong, Dang Xuan; Vinh, Phan Thi Khanh (Free Radicals and Antioxidants)
Introduction: This study focused on the discussion of effect of various extraction conditions for phlorotannin content and antioxidant activities extracted from brown algae Sargassum serratum. The algae was grown in the tropical coastal areas of Vietnam. Methods: The various extraction conditions include the following parameters: temperature (30-800C), maceration time (1/2–2,5 hours; 8-48 hrs), the ratio of solvent to material (10:1–70:1 (v/w)), pH (2–8), various kind of solvents (ethanol, acetone, chloroform, ethyl acetate and n-hexan) and solvent concentrations. Phlorotannin content, antioxidant activities, and some phytochemical compositions of Sargassum serratum were evaluated. Results: The highest phlorotannin content and antioxidant activities was expressed when extracting in the following conditions: 100% ethanol solvent at 500C in 32 hours with the ratio of solvent to material of 40/1 (v/w), pH 7 and one-step extraction. The extract contained flavonoid, terpenoid, alkaloid, fatty and oil. DPPH free radical scavenging of the extract was 87.53%. Conclusion: Phlorotannin content and antioxidant activities extracted from Sargassum serratum was depended on the extracting conditions. The condition of extraction for antioxidant phlorotannin and the chemical composition of extract was determined. Brown algae Sargassum serratum has high antioxidant phlorotannin content. A total of 6 compounds were identified from the extract of Sargassum serratum.
Keywords: Antioxidant; Brown algae; Extraction; Phlorotannin; Sargassum